Hepatocellular carcinoma targeted therapy and multidisciplinary care - McMasters, Kelly M.; Vauthey, Jean-Nicolas.; SpringerLink (Online service). (Totowa, N.J. London Humana Springer [distributor], 2011)
"Hepatocellular Carcinoma: Targeted Therapy" provides a detailed repository of the latest information regarding HCC epidemiology, diagnosis, imaging, pathology, staging, and treatment options. This volume also provides an up-to-date guide for treatment that explores not only traditional treatments, but newer investigational treatment options including, surgical resection, liver transplantation, ablation (radiofrequency, microwave), percutaneous ethanol or acetic acid injection, transarterial chemoembolization (TACE), intra-arterial radiation therapy, and systemic chemotherapy."
Epidemiology and pathogenesis of hepatocellular carcinoma -- Biology of hepatocellular carcinoma -- Hepatocellular cancer: pathologic considerations -- Screening program in high-risk populations -- Staging of hepatocellular carcinoma -- Multidisciplinary care of the hepatocellular carcinoma patient -- Evidence-based guidelines for treatment of hepatocellular carcinoma in Japan -- Hepatocellular carcinoma arising in the non-viral, non-alcoholic liver -- Liver resection for hepatocellular carcinoma -- Ultrasound-guided liver resection for hepatocellular carcinoma -- Portal vein embolization prior to resection -- Laparoscopic liver resection for HCC: a European perspective -- Laparoscopic liver surgery for the management of hepatocellular carcinoma: the American perspective -- Liver transplant for hepatocellular carcinoma -- Vascular resection for hepatocellular carcinoma -- Radiofrequency ablation for hepatocellular carcinoma -- Microwave ablation and hepatocellular carcinoma -- Transarterial chemoembolization -- Chemoembolization with drug-eluting beads -- Yttrium-90 radioembolotherapy for hepatocellular carcinoma -- Cytotoxic chemotherapy and endocrine therapy for hepatocellular carcinoma -- Targeted therapies for hepatocellular carcinoma -- The future: combination systemic therapy for hepatocellular carcinoma -- Follow-up and salvage therapy for recurrent hepatocellular carcinoma.
Electronic reproduction.
Keywords: Liver -- Cancer -- Treatment; Drug targeting; Electronic books